Desenvolvimento de equipamento para ensaio de tribocorrosão e análise de revestimentos superficiais em aço inoxidável super duplex SAF 2507 depositados por processo TIP/TIG em base de aço ASTM A36 - Lesniesky, Roberto Junior Gaspar (2021)
This work presents the design of a linear tribometer for the analysis of high corrosion resistance metallic alloy coatings, validated by analyzing the SAF 2507 superduplex stainless steel. The test is based on the surface corrosion of the material immersed in NaCl medium at a concentration of 1 mol/L subjected to an electric current potential controlled by a potentiostat in accordance with ASTM G61. The study evaluated SAF 2507 superduplex alloy deposits on ASTM A36 carbon steel base plates deposited by the TIP/TIG process with addition electrode oscillation frequencies of 5Hz, 10Hz and 15Hz. The study developed a machine to generate friction in order to evaluate the effects of tribocorrosion during the voltammetry test and compare to voltammetry tests performed on samples of the same material with a polished surface. Applications for these coatings span the oil and gas, chemical and pulp and paper industries. The results and analyzes compared the microstructure and post-processing characteristics of the material analyzed, the effects of pitting and crevice corrosion on the microstructure were analyzed by microscopy, highlighting the effects of friction on layer rupture, forming pits in the friction region and consequently reducing corrosion resistance. It is pertinent to highlight the proper electromechanical functioning of the equipment, as well as the coupled instrumentation, allowing control of process parameters, the equipment was submitted to a patent of invention.